Reactive dye removal from simulated wastewater using tetrabutyl ammonium bromide as an extractant - Othman, Norasikin (Penerbit UTM Press, 2014)
Dyes caused serious environmental pollution and health problem in many ways. Many dyes have toxic effects on aquatic life and also on humans. Liquid-liquid extraction process is one of the alternatives for dye removal from wastewater. Removal of remazol red 3BS from simulated textile wastewater using tetrabutyl ammonium bromide has been studied at room temperature with total operation time of 18 hours. Several parameters have been studied such as pH, diluents, initial dye concentration, extractant concentration and stripping agents toward the extraction process of the dye. The results show only small effects of pH on the extraction percentage. The best diluent for the extraction is dichloromethane with the percentage of 98%. The percentage of extraction is maximum (97%) at 0.07M of TBAB concentration with the distribution ratio of D= 34.65. Salicylic acid in Na2CO3 with the ratio of 1:2 gives the highest percentage of stripping process. It shows a good performance for liquid-liquid extraction of remazol red 3BS for both removal and recovery processes.